A new small Drawida Michaelsen, 1900 (Clitellata: Moniligastridae) species from the Western Ghats of Kerala State, India - Ardra, Rajendran Menon; Narayanan, S. Prasanth; Kumar, P. Sunil; Sudhikumar, A.v.; Thomas, A.p. (Zootaxa, 2026)
The genus Drawida Michaelsen, 1900, is a large genus naturally restricted to the South, Southeast and East Asian region, with three widespread cosmopolitan species. A new earthworm species of Drawida namely, D. vazhania Ardra & Narayanan, sp. nov., is described from materials collected from the Vazhani Dam area situated in Thrissur District of the Kerala state, south-western India. With small body size, position of the secondary male apertures between setal lines BC, presence of genital tumescence in male field, eversible penes, glandular prostates, with distinct spermathecal atrium and absence of internal accessory glands associated with genital tumescence, the new species belongs to Barwelli species group. Together with the new species described herein, this group has a total of seven species. Among the congeners of the group, D. vazhania sp. nov. shows close similarity with D. barwelli (Beddard, 1886). D. vazhania sp. nov. can be easily differentiated from the other members of the Barwelli species group by the presence of grooved male genital field, by the kidney or bean-shaped prostate and narrow tubular, C-shaped prostatic capsule and distinct small, sessile atrium on body wall. Present work provides detailed description of the external and internal characteristics, images, illustrations of the key features and with a distributional map. With the new finding, a total number of Drawida species found in India and the Western Ghats Biodiversity hotspot has gone up to 82 and 54 respectively.